The Effect of Communication Skills on Career Choices Among Hospitality Vocational Students in Jakarta - Fani NurJana; Riswano; Jaka Marsita (Universitas Airlangga, 2026)
Background: Uncertainty and doubt in making career decisions remain a problem experienced by vocational students in the field of hospitality. The phenomenon is frequently the result of low self-esteem regarding students' communication abilities, particularly in foreign language learning, interpersonal sensitivity, and social adaptation. Consequently, they would rather not take up positions that involve direct contact with guests. Objective: This study aims to determine the effect of communication skills on the career choices of vocational (SMK) students majoring in hospitality in Jakarta. Method: This study employed a quantitative method with an associative research design. The sample consisted of 134 students from Grade XI and XII of the Hospitality Accommodation program at SMK Negeri 33 Jakarta. The data were gathered through questionnaires and processed using SPSS software. The analysis encompassed prerequisite tests, simple linear regression, and the determination of the coefficient of determination. Results: The results show that communication skills positively influence students' career choices, and the effect is statistically significant (p = 0.000), which is less than 0.05. The regression coefficient of 0.537 implies that increasing communication skills by one unit would raise the likelihood of career choices by 0.537. Furthermore, communication skills account for 26.3% of the variance in career choice decisions, with the remaining variance explained by other factors. Conclusion: The higher the students' communication mastery, the more mature their career decisions. The findings of this research suggest that a shift in the curriculum is necessary, one that will not only emphasize hard skills but also provide thorough training in interpersonal communication as a means of empowering and mentally preparing students to tackle the job market. Keywords: Career Choice; Communication Skills; Hospitality Vocational School; Vocational Education.